Prionohydrus cambyreta sp. nov. from Iberá wetlands—the first species of the genus from northern Argentina (Coleoptera: Noteridae) - Urcola, Juan I.; Baca, Stephen M.; Rodriguez, Georgina; Michat, Mariano C. (Zootaxa, 2024)
Prionohydrus cambyreta sp. nov. is described from the Iberá wetlands, Corrientes Province, Argentina. Diagnostic characters are described and illustrated in detail, and the new taxon is compared with the other four South American species of Prionohydrus Gómez & Miller, 2013. In external appearance, P. cambyreta is very similar to P. matogrossensis Gómez & Miller 2013, but it can be distinguished by the shape of the male genitalia. The new species represents the most southern record for Prionohydrus, extending the distributional range of the genus by about 1700 km.